2020
DOI: 10.1111/jan.14655
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of the application of heat and pressure on peripheral venous cannulation in adults: A randomized controlled trial

Abstract: Aim To evaluate the effectiveness of the application of topical heat, high pressure or a combination of both on antebrachial venous cannulation. Design A cross‐over clinical trial blinded for haemolysis analysis. Methods This cross‐over clinical trial with two periods was performed in the Clinical Trial Unit of Hospital Universitario de La Princesa (Madrid) during June–July of 2017 in 59 healthy adults who were randomly allocated to one of three interventions: (1) Using dry topical heat for 7 min produced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(94 reference statements)
1
1
0
Order By: Relevance
“…In the same line of our results a study by Simón-López et al (2021) studied the "Benefits of the application of heat and pressure on peripheral venous cannulation in adults" concluded that application of dry heat for 7 min what resulted in 1.92 times more effective than other methods.…”
Section: Socio-demographic Characteristicssupporting
confidence: 79%
See 1 more Smart Citation
“…In the same line of our results a study by Simón-López et al (2021) studied the "Benefits of the application of heat and pressure on peripheral venous cannulation in adults" concluded that application of dry heat for 7 min what resulted in 1.92 times more effective than other methods.…”
Section: Socio-demographic Characteristicssupporting
confidence: 79%
“…Also it has been observed over a period of two years working as a clinical instructor in Medical Surgical Department with Nursing students that most patients with chemotherapy treatment experience severe discomfort caused by frequent cannulation because of the bad condition of their veins. It has been reported that the local application of heat before catheter insertion provides vasodilation and venous distension that improve the experience of cannulation (Simón-López, et al,2021). It is hoped that the current study open the door for evidence based practice and determine the effect of moist heat on veins integrity and experienced pain while undergoing peripheral intravenous cannulation among these patients.…”
Section: Hospitalizedmentioning
confidence: 80%